Breaking barriers to climate finance: asymmetric nexus between green investment and energy innovation in Europe - Jiu, Jingli; Ali, Sajid; Nazar, Raima; Khan, Ahmad Imran (Elsevier, 2024)
Growing concerns regarding climate change and the necessity to shift towards a low-carbon economy have resulted in a significant rise in the worth of green finance for developing energy technology. This growing emphasis on green finance underscores the urgency for a nuanced exploration of the asymmetric nexus between green investment and energy innovation in Europe. The present article investigates the asymmetric relationship between green investment and energy innovation in the top ten European nations with the highest green investment (France, Netherlands, Germany, Italy, Spain, Denmark, Austria, Finland, the UK, and Sweden). Formerly, panel data methodologies were employed to observe the link between green investment and energy innovation despite the absence of an exclusive connection in certain economies. On the other hand, this study uses ‘Quantile-on-Quantile’ approach for econometric estimation using the annual data from 2007 to 2022. This unique methodology enables a detailed and specific analysis of time-series interdependence in every economy, providing valuable perceptions of the nuanced relationship between these variables. Investment in renewable energy is employed as a proxy for green investment, while energy-related patents represent energy innovation. The study employs a quantile cointegration test to assess the variables long-run relationship. The results indicate a positive correlation between green investment and energy innovation in many countries at certain data points. Additionally, the analysis demonstrates that the extent of asymmetry between these variables varies across countries, stressing policymakers' need to closely monitor fluctuations in green investment and energy innovation.